Distribution of Extracellular Matrix Molecules in Human Uterine Tubes During the Menstrual Cycle: A Histological and Immunohistochemical Analysis - Orihuela-Diaz, P; Godoy-Guzman, C (Blackwell Publishing Ltd, 2018)
The uterine tube (UT) is an important and complex organ of the women s reproductive system. In general, the anatomy and basic histology of this organ are well-known. However, the composition and function of the extracellular matrix (ECM) of the UT is still poorly understood. The ECM is a complex supramolecular material produced by cells which is commonly restricted to the basement membrane and interstitial spaces. ECM molecules play not only a structural role, they are also important for cell growth, survival and differentiation in all tissues. In this context, the aim of this study was to evaluate the deposition and distribution of type I and III collagens and proteoglycans (decorin, biglycan, fibromodulin and versican) in human UT during the follicular and luteal phases by using histochemical and immunohistochemical techniques. Our results showed a broad synthesis of collagens (I and III) in the stroma of the UT. The analysis by regions showed, in the mucosa, a specific distribution of versican and fibromodulin in the epithelial surface, whereas decorin and fibromodulin were observed in the lamina propria. Versican and decorin were found in the stroma of the muscular layer, whereas all studied proteoglycans were identified in the serosa. Curiously, biglycan was restricted to the wall of the blood vessels of the serosa and muscular layers. Furthermore, there was an immunoreaction for collagens, decorin, versican and fibromodulin in the UT peripheral nerves. The differential distribution of these ECM molecules in the different layers of the UT could be related to specific structural and/or biomechanical functions needed for the oviductal transport, successful fertilization and early embryogenesis. However, further molecular studies under physiological and pathological conditions are still needed to elucidate the specific role of each molecule in the human UT. © 2018 Anatomical Society